Contribution of Land Water Storage Change to Regional Sea-Level Rise Over the Twenty-First Century - Karabil, Sitar; Sutanudjaja, Edwin H.; Lambert, Erwin; Bierkens, Marc F. P.; Van de Wal, Roderik S. W. (Frontiers in Earth Science, 2021)
Change in Land Water Storage (LWS) is one of the main components driving sea-level rise over the 21st century. LWS alteration results from both human activities and climate change. Up to now, climate change-induced LWS and the resultant contribution to regional sea-level changes have not been quantified. This study, for the first time, explores the possible range of LWS contributions across climate scenarios to global and regional sea-level change by the end of the 21st century. For this quantification, we investigated the contribution of LWS change to regional sea-level rise by considering five different climate models forced by three different climate scenarios over the 21st century. Our results suggest that LWS change will contribute around 10% to the projected global mean sea-level rise by the end of 21st century. The contribution of LWS to regional sea-level rise is projected to be considerably larger than the global mean over several regions including Pacific islands, the south coast of Africa and the west coast of Australia.